Rancang Bangun Client-Side Mobile Web App Menggunakan JQuery Mobile - Seng Hansun (Universitas Multimedia Nusantara, 2013)
Mobile operating system market shares always grow from year to year. The issue to make a mobile application in an easy, fast, and reliable way had arisen. Therefore, many UI framework to create mobile web application have been introduced, one of them is jQuery Mobile. jQuery Mobile with its’ ‘write less, do more’ slogan become popular among web mobile developers. In this paper, the author tries to build a stand-alone mobile application using jQuery Mobile as a prototype of Universitas Multimedia Nusantara mobile application. It can be concluded that jQuery Mobile can be used to make a simple application in a fast and rapid changing environment. Kata kunci—jQuery Mobile, web mobile app, HTML, CSS, JavaScript